If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 1 = 3y + -1 Reorder the terms: 1 + 4y = 3y + -1 Reorder the terms: 1 + 4y = -1 + 3y Solving 1 + 4y = -1 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 1 + 4y + -3y = -1 + 3y + -3y Combine like terms: 4y + -3y = 1y 1 + 1y = -1 + 3y + -3y Combine like terms: 3y + -3y = 0 1 + 1y = -1 + 0 1 + 1y = -1 Add '-1' to each side of the equation. 1 + -1 + 1y = -1 + -1 Combine like terms: 1 + -1 = 0 0 + 1y = -1 + -1 1y = -1 + -1 Combine like terms: -1 + -1 = -2 1y = -2 Divide each side by '1'. y = -2 Simplifying y = -2
| Sqrt(x^2+6)+sqrt(7x)=0 | | 5(1+3m)=10(X-1) | | 9(f+6)= | | 6*(3a+b)= | | 5e+7= | | 56=1/2b(14) | | 1011=5 | | -16x^2+15x-88=0 | | -9+2=18 | | 2y-3(5y-1)=3-4(1-y) | | 3(X-7)=3(3-9n) | | sinx=5/2 | | 552.8(-0.1)= | | 4+494736382= | | 2a+2a^2=84 | | 12x+40=184 | | 10/2x=5x | | 3(2x+5)=333 | | 7x^2+12x+8=5x^2+7x+8 | | f(x)=sqrt(2x+1) | | -1÷2/4= | | 9x-8(x-9)+7(y-9)= | | 12x^2-24x+12= | | -1÷2/4 | | 8x-14=8x | | (9ab/10b^3)*(2b/3a) | | b2-4/2=10 | | 4/5x-214 | | m^2-4m=5m-8 | | 13/m=2/9 | | 8(4x+4)=-5x-32 | | 6+4=(6x+9)/3 |